Pengembangan Materi PAI Berbasis Kontekstual Untuk Meningkatkan Pemahaman Peserta Didik - Andi Fitriani Djollong; Kurnia Alex; Fitriani Muh Amin; Nursia Nursia; Yenni Yenni; Juhariati Juhariati; Misbah Misbah (Journal of Humanities, Social Sciences, and Education, 2026)
The development of contextual-based Islamic Religious Education (PAI) materials is an important strategy in improving students' understanding of Islamic values in a more meaningful and applicable way. This study aims to analyze various literature reviews related to the development of contextual-based PAI materials in improving students' understanding. The study used a library research method by examining 24 scientific articles, national journals, and relevant academic sources that discuss contextual learning in PAI. Data were analyzed using content analysis techniques to find patterns, concepts, and main findings from various previous studies. The results of the study indicate that the development of contextual-based PAI materials is able to: (1) connect learning materials with students' real experiences; (2) increase students' active involvement and learning motivation; (3) strengthen students' critical and reflective thinking skills; (4) help internalize Islamic values in everyday life; and (5) improve learning outcomes and a deeper understanding of religious concepts. For example, teachers can implement contextual-based PAI materials through discussions of daily life cases, integration of local cultural values, and the use of digital learning media in classroom activities. The contextual approach also allows teachers to integrate local culture, social environment, and digital technology into learning materials so that learning becomes more relevant to the needs of students in the modern era. Thus, developing contextual Islamic Religious Education (PAI) materials can be an innovative alternative for creating effective, meaningful, and real-life-oriented religious learning for students.